SISTEM INFORMASI PENERIMAAN SISWA BARU BERBASIS WEB PADA SMP USWATUN HASANAH JAKARTA - Utami, Dian; Agustina, Nani (STMIK ANTAR BANGSA, 2015)
Abstract— Looking at the development of technology in the world, especially in the field of computers, Uswatun Hasanah Jakarta Junior High School felt the need to implement an information system for the admission of new students. Admission Information System Web-Based In Jakarta Hasanah Uswatun SMP is designed to simplify and accelerate the process of new admissions and improving the safety and accuracy of the data. SMP Uswatun Hasanah Jakarta is the school admissions system is still new ways to wear it manually by simply having problems because the new admissions in SMP Uswatun Hasanah. By because it, the author tries to make a new admissions website for SMP Uswatun Hasanah. Acceptance of new student information system web based it easy for prospective students to provide information that knows no boundaries of place and time continuously. In addition, the information can be presented in a detailed and up to date.Intisari - Melihat perkembangan teknologi di dunia terutama dibidang komputer, Sekolah SMP Uswatun Hasanah Jakarta merasa perlu untuk menerapkan sebuah sistem informasi untuk bagian penerimaan siswa baru. Sistem Informasi Penerimaan Siswa Baru Berbasis Web Pada SMP Uswatun Hasanah Jakarta dirancang untuk mempermudah dan mempercepat proses penerimaan siswa baru serta meningkatkan keamanan dan keakuratan data. SMP Uswatun Hasanah Jakarta adalah sekolah yang sistem penerimaan siswa barunya masih memakai cara manual oleh karna itu cukup mengalami kendala dalam penerimaan siswa baru di SMP Uswatun Hasanah. Oleh karna itu, penulis mencoba membuat website penerimaan siswa baru untuk SMP Uswatun Hasanah.Sist em Informasi Penerimaan siswa baru berbasis web memberikan kemudahan bagi calon siswa dalam memberikan informasi yang tak mengenal batas tempat dan waktu terus menerus. Selain itu, informasi yang ada dapat disajikan secara terperinci dan up to date.Kata kunci : Penerimaan Siswa Baru, Informasi, Website